Properties of Enterococcus faecalis, a new probiotic bacterium isolated from the intestine of snakehead fish (Channa striatus Bloch) - Allameh, Sayyed Kamaleddin; Ringo, Einar; Md. Yusoff, Fatimah; Mohd Daud, Hassan; Ideris, Aini (Academic Journals, 2014)
Bacterial and other microbial contamination of fresh vegetables from the farm or garden to the market and to the final consumer remain a problem worldwide. This study was designed to evaluate the various possible bacterial species responsible for the contamination of Brassica oleracea var. capitata (cabbage) in the Korle-Bu vegetable garden and Agbogbloshie market in the Accra Metropolis, Ghana. Sixty (60) cabbage samples were collected and investigated bacteriologically using standard Food and Agriculture Organization (FAO) of the United Nations (UN) total aerobic plate count methods.Cabbage samples from the vegetable garden were found to be more contaminated than the market with a total mean colony count of 2.43×106 CFU/g and 1.53×106 CFU/g respectively. Staphylococcus aureus was the most predominant bacteria isolated with a high percentage occurrence of 51% followed by Escherichia coli (28%), Bacillus sp. (12%), Streptococcus sp. (5%), and Pseudomonas aeruginosa (4%). From the study, bacterial contamination of cabbage grown at the Korle-Bu vegetable garden and the Agbogbloshie market were all above the recommended standard levels especially E. coli which should be less than 10 bacteria per gram. Therefore it is recommended that these vegetables be thoroughly washed with safe water or saline solutions before processing and consumption especially where they are not going to be heated or cooked before consumption.